Anti-crack road concrete and preparation method thereof

By adding specific formulas and additives to asphalt concrete, the problems of poor resistance to asphalt concrete pavement and insufficient crack resistance at high temperatures are solved, and higher high-temperature resistance and crack resistance are achieved, extending the service life of the pavement.

CN119461989AActive Publication Date: 2025-02-18HEBEI LONGSHENG NEW BUILDING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510031726.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-18
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing asphalt concrete pavement has poor resistance at high temperatures and is difficult to withstand repeated vehicle loads, making it prone to looseness, deformation and cracks.

Method used

A crack-resistant road concrete formula, including asphalt, waste asphalt, gravel, medium sand, cement, lignin, carbon fiber powder, lene powder and additives (ethylene-vinyl acetate copolymer and hydroxyoctadecanol hydroxy hardness ) improves the high temperature resistance and crack resistance of concrete by adjusting the weight ratio of the additive and the surface modification of carbon fiber powder.

Benefits of technology

It achieves good high-temperature resistance and crack resistance of crack-resistant road concrete, extends the service life of the road surface and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and provides anti-crack road concrete and a preparation method thereof. The anti-crack road concrete is prepared from the following components in parts by weight: 25 to 30 parts of asphalt, 10 to 15 parts of a waste asphalt material, 110 to 120 parts of broken stone, 45 to 55 parts of medium sand, 15 to 25 parts of cement, 5 to 15 parts of lignin, 10 to 20 parts of carbon fiber powder, 15 to 25 parts of pyrophyllite powder and 10 to 16 parts of an auxiliary agent, the auxiliary agent is prepared from an ethylene-vinyl acetate copolymer and hydroxyeicosanol hydroxy stearate; the weight ratio of the ethylene-vinyl acetate copolymer to the hydroxyeicosanol hydroxystearate is (1: 4)-(7: 1). According to the technical scheme, the problems of poor high temperature resistance and poor crack resistance of the anti-crack road concrete in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a crack-resistant road concrete and a preparation method thereof. Background Art

[0002] Road concrete is a composite material commonly used in construction projects, and aggregates are usually cemented into a whole by cementing materials. According to the materials used for the pavement and the construction process, road concrete can be divided into two categories: cement concrete and asphalt concrete. Among them, the vast majority of pavements use asphalt concrete. The pavement formed by asphalt concrete usually has the advantages of being flat and seamless, with low driving vibration, low noise, and good driving comfort. Among them, the material of the asphalt concrete pavement can be recycled, which is helpful for environmental protection and resource conservation. However, asphalt concrete pavement also has some defects. The high temperature resistance of asphalt concrete is poor, and the pavement formed by asphalt concrete is difficult to withstand the repeated effects of vehicle loads, especially large load external forces. Under long-term action, there will be looseness, deformation, and longitudinal and transverse cracks. Therefore, a road concrete is developed with good high temperature resistance and crack resistance, which is important for extending the service life of the road concrete pavement and reducing the economic losses caused by maintaining the pavement. Summary of the invention

[0003] The present invention provides a crack-resistant road concrete and a preparation method thereof, which solves the problems of poor high temperature resistance and poor crack resistance of the crack-resistant road concrete in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a crack-resistant road concrete, comprising the following components in parts by weight: 25-30 parts of asphalt, 10-15 parts of waste asphalt, 110-120 parts of crushed stone, 45-55 parts of medium sand, 15-25 parts of cement, 5-15 parts of lignin, 10-20 parts of carbon fiber powder, 15-25 parts of pyrophyllite powder, and 10-16 parts of additives; The auxiliary agent includes ethylene-vinyl acetate copolymer and octacosanol hydroxystearate; The weight ratio of the ethylene-vinyl acetate copolymer to octacosanol hydroxystearate is 1:4-7:1.

[0005] As a further technical solution, the weight portion of the ethylene-vinyl acetate copolymer is greater than the weight portion of the hydroxyoctacosanol hydroxystearate.

[0006] In the present invention, when the weight portion of ethylene-vinyl acetate copolymer is greater than the weight portion of hydroxyoctacosanol hydroxystearate, the high temperature resistance and crack resistance of the crack-resistant road concrete can be further improved.

[0007] As a further technical solution, the weight ratio of the ethylene-vinyl acetate copolymer to the hydroxyoctacosanol hydroxystearate is 2-5:1.

[0008] By adjusting the weight ratio of ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate, when the weight ratio of ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate is 2~5:1, the synergistic effect of the two can reach the optimal level, which can further improve the high temperature resistance and crack resistance of the crack-resistant road concrete.

[0009] As a further technical solution, the carbon fiber powder is modified carbon fiber powder, and the raw materials of the modified carbon fiber powder include carbon fiber powder and 2-acetamidoacrylic acid.

[0010] In the present invention, the inventors found that the surface modification of carbon fiber powder by 2-acetamidoacrylic acid can further improve the high temperature resistance and crack resistance of crack-resistant road concrete. The reason may be that after the surface modification of carbon fiber powder by 2-acetamidoacrylic acid, the carbon fiber powder can be dispersed more evenly in asphalt and filler, thereby making the force inside the concrete more uniform, which can also reduce the damage to the concrete caused by uneven force, thereby further improving the high temperature resistance and crack resistance of crack-resistant road concrete.

[0011] As a further technical solution, the weight ratio of the carbon fiber powder to 2-acetamidoacrylic acid is 20:1-3.

[0012] When the weight ratio of carbon fiber powder to 2-acetamidoacrylic acid is 20:1-3, the high temperature resistance and crack resistance of the crack-resistant road concrete can be further improved.

[0013] As a further technical solution, the preparation method of the modified carbon fiber powder comprises the following steps: dissolving the 2-acetamidoacrylic acid in ethanol, adding the carbon fiber powder, mixing evenly, and drying to obtain the modified carbon fiber powder.

[0014] As a further technical solution, the crushed stone is one or more of basalt crushed stone, diabase crushed stone, and granite crushed stone.

[0015] As a further technical solution, the particle size of the crushed stone is 10~20mm.

[0016] As a further technical solution, the medium sand is one or both of quartz sand and basalt sand.

[0017] As a further technical solution, the particle size of the medium sand is 0.3~0.45mm.

[0018] As a further technical solution, the particle size of the pyrophyllite powder is 10~44μm.

[0019] As a further technical solution, the waste asphalt material comes from Grade III aged petroleum asphalt pavement, with a viscosity value of 1.5-1.9 Pa.s at 135°C and a needle penetration value of 18-23 at 25°C.

[0020] In the present invention, the needle penetration value of the waste asphalt material is measured at 0.1 mm at 25° C., a load of 100 g, and a penetration time of 5 s.

[0021] The present invention also proposes a method for preparing the crack-resistant road concrete, comprising the following steps: S1. Preheat the remaining components except asphalt and additives, mix them evenly, and obtain a mixture; S2. Evenly mix the mixture, the asphalt and the additive to obtain the anti-cracking road concrete.

[0022] As a further technical solution, in step S1, the preheating temperature is 145-155°C; in step S2, when the mixing is uniform, the temperature is 150-160°C, the stirring time is 1-2h, and the rotation speed is 900-1100r / min.

[0023] The working principle and beneficial effects of the present invention are: In the present invention, asphalt is combined with waste asphalt, crushed stone, medium sand, cement, lignin, carbon fiber powder, pyrophyllite powder and additives, which can realize the effective combination of filler and asphalt, and also realize the reuse of waste asphalt to a certain extent, thereby obtaining a crack-resistant road concrete with a dense and stable internal structure, which has good high temperature resistance and good crack resistance. Among them, the additives include ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate, and the ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate have a synergistic effect. In the process of combining with asphalt, a mesh structure can be formed, which can promote the combination of asphalt and filler, improve the overall stability of asphalt, and then improve the high temperature resistance and crack resistance of the crack-resistant road concrete. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In the following embodiments and comparative examples, the asphalt is petroleum asphalt, model 70#; the waste asphalt material comes from Grade III aged petroleum asphalt pavement, with a viscosity value of 1.8 Pa.s at 135°C and a needle penetration value of 20 at 25°C; the crushed stone is basalt crushed stone with an average particle size of 15 mm; the medium sand is quartz sand with an average particle size of 0.4 mm; the cement is ordinary Portland cement, model PO42.5; the particle size of talc powder is 15 μm; the model of lignin is JL8544, purchased from Hefei Bomei Biotechnology Co., Ltd.; the particle size of carbon fiber powder is 13 μm; the model of ethylene-vinyl acetate copolymer is V961RC.

[0026] Example 1 A crack-resistant road concrete comprises the following components in parts by weight: 25 parts of asphalt, 10 parts of waste asphalt, 110 parts of basalt crushed stone, 45 parts of quartz sand, 15 parts of cement, 5 parts of lignin, 10 parts of carbon fiber powder, 15 parts of pyrophyllite powder, and 10 parts of additives; The auxiliary agent includes 2 parts of ethylene-vinyl acetate copolymer and 8 parts of hydroxyoctadecanoyl hydroxystearate; The preparation method thereof comprises the following steps: S1. Preheat the remaining components except the asphalt and the additive to 145° C. and mix them evenly to obtain a mixture; S2. Stir the mixture, asphalt and additives at 150° C. and 900 r / min for 2 h to mix them evenly to obtain crack-resistant road concrete.

[0027] Example 2 A crack-resistant road concrete comprises the following components in parts by weight: 28 parts asphalt, 13 parts waste asphalt, 115 parts basalt crushed stone, 50 parts quartz sand, 20 parts cement, 10 parts lignin, 15 parts carbon fiber powder, 20 parts pyrophyllite powder, 12 parts additives; The auxiliary agent includes 6 parts of ethylene-vinyl acetate copolymer and 6 parts of hydroxyoctacosanol hydroxystearate; The preparation method thereof comprises the following steps: S1. Preheat the remaining components except the asphalt and the additive to 150° C. and mix them evenly to obtain a mixture; S2. Stir the mixture, asphalt and additives at 155°C and a speed of 1000 r / min for 1.5 h to mix them evenly to obtain crack-resistant road concrete.

[0028] Example 3 A crack-resistant road concrete comprises the following components in parts by weight: 30 parts of asphalt, 15 parts of waste asphalt, 120 parts of basalt crushed stone, 55 parts of quartz sand, 25 parts of cement, 15 parts of lignin, 20 parts of carbon fiber powder, 25 parts of pyrophyllite powder, 16 parts of additives; The auxiliary agent includes 14 parts of ethylene-vinyl acetate copolymer and 2 parts of hydroxyoctadecanoyl hydroxystearate; The preparation method thereof comprises the following steps: S1. Preheat the remaining components except asphalt and additives to 155° C. and mix them evenly to obtain a mixture; S2. Stir the mixture, asphalt and additives at 160° C. and a speed of 1100 r / min for 1 h to mix them evenly to obtain crack-resistant road concrete.

[0029] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the auxiliary agent includes 4 parts of ethylene-vinyl acetate copolymer and 8 parts of hydroxyoctacosanol hydroxystearate.

[0030] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the auxiliary agent includes 7 parts of ethylene-vinyl acetate copolymer and 5 parts of hydroxyoctacosanol hydroxystearate.

[0031] Example 6 The only difference between this embodiment and embodiment 5 is that in this embodiment, the auxiliary agent includes 11 parts of ethylene-vinyl acetate copolymer and 1 part of hydroxyoctacosanol hydroxystearate.

[0032] Example 7 The only difference between this embodiment and embodiment 5 is that in this embodiment, the auxiliary agent includes 8 parts of ethylene-vinyl acetate copolymer and 4 parts of hydroxyoctacosanol hydroxystearate.

[0033] Example 8 The only difference between this embodiment and embodiment 5 is that in this embodiment, the auxiliary agent includes 10 parts of ethylene-vinyl acetate copolymer and 2 parts of hydroxyoctacosanol hydroxystearate.

[0034] Example 9 The only difference between this embodiment and Embodiment 8 is that in this embodiment, the carbon fiber powder is modified carbon fiber powder, and its preparation method includes the following steps: after dissolving 0.5 parts of 2-acetamidoacrylic acid in 25 parts of ethanol, adding 20 parts of carbon fiber powder, mixing evenly, and drying to obtain modified carbon fiber powder.

[0035] Example 10 The difference between this embodiment and embodiment 9 is that, in this embodiment, 3.5 parts of 2-acetamidoacrylic acid are added.

[0036] Embodiment 11 The difference between this embodiment and embodiment 9 is that, in this embodiment, 1 part of 2-acetamidoacrylic acid is added.

[0037] Example 12 The difference between this embodiment and embodiment 9 is that, in this embodiment, 3 parts of 2-acetamidoacrylic acid are added.

[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the auxiliary agent only includes ethylene-vinyl acetate copolymer.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that, in this comparative example, the auxiliary agent only includes hydroxyoctacosanol hydroxystearate.

[0040] Comparative Example 3 The only difference between this comparative example and Example 1 is that no auxiliary agent is added in this comparative example.

[0041] Experimental Example 1 High temperature resistance test The crack-resistant road concrete prepared in Examples 1 to 12 and Comparative Examples 1 to 3 was subjected to a high-temperature rutting dynamic stability test according to the method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering", wherein the concrete sample size was 300 mm × 300 mm × 100 mm, the test temperature was 60°C, the wheel pressure was 0.7 MPa, the total applied load was 780 N, and the test result was the average value of 3 samples.

[0042] Experimental Example 2 Crack resistance test The crack-resistant road concrete prepared in Examples 1 to 12 and Comparative Examples 1 to 3 was tested for splitting tensile strength according to the method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering", wherein the concrete specimen was a cylindrical specimen with a diameter of 100 mm and a height of 40 mm, the test temperature was 15° C., the loading rate was 50 mm / min, and the test result was the average value of 3 specimens.

[0043] The test results are shown in Table 1 below: Table 1 Performance test results of Examples 1 to 12 and Comparative Examples 1 to 3

[0044] Compared with Comparative Examples 1 to 3, the high-temperature rutting dynamic stability and splitting tensile strength of Example 1 are significantly improved, indicating that when the additives include ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate, the ethylene-vinyl acetate copolymer and hydroxyoctacosanol hydroxystearate have a synergistic effect, which can improve the high temperature resistance and crack resistance of the crack-resistant road concrete.

[0045] Compared with Examples 2 and 4, the high-temperature rutting dynamic stability and splitting tensile strength of Examples 5 to 8 are improved, indicating that when the weight of ethylene-vinyl acetate copolymer is greater than the weight of hydroxyoctadecanoyl hydroxystearate, the high temperature resistance and crack resistance of the crack-resistant road concrete can be further improved.

[0046] Compared with Examples 5 to 6, the high-temperature rutting dynamic stability and splitting tensile strength of Examples 7 to 8 are improved, indicating that when the weight ratio of ethylene-vinyl acetate copolymer to hydroxyoctadecanoyl hydroxystearate is 2 to 5:1, the high-temperature resistance and crack resistance of the crack-resistant road concrete can be further improved.

[0047] Compared with Example 8, the high-temperature rutting dynamic stability and splitting tensile strength of Examples 9 to 12 are improved, indicating that surface modification of carbon fiber powder using 2-acetamidoacrylic acid can further improve the high-temperature resistance and crack resistance of crack-resistant road concrete.

[0048] Compared with Examples 9 to 10, the high-temperature rutting dynamic stability and splitting tensile strength of Examples 11 to 12 are improved, indicating that when the weight ratio of carbon fiber powder to 2-acetamidoacrylic acid is 20:1 to 3, the high-temperature resistance and crack resistance of the crack-resistant road concrete can be further improved.

[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A crack-resistant road concrete, characterized in that: The composition comprises the following components in parts by weight: 25-30 parts of asphalt, 10-15 parts of waste asphalt, 110-120 parts of crushed stone, 45-55 parts of medium sand, 15-25 parts of cement, 5-15 parts of lignin, 10-20 parts of carbon fiber powder, 15-25 parts of pyrophyllite powder, and 10-16 parts of additives; The auxiliary agent includes ethylene-vinyl acetate copolymer and octacosanol hydroxystearate; The weight ratio of the ethylene-vinyl acetate copolymer to octacosanol hydroxystearate is 1:4-7:

1.

2. The anti-cracking road concrete according to claim 1, characterized in that: The weight portion of the ethylene-vinyl acetate copolymer is greater than the weight portion of the hydroxyoctacosanol hydroxystearate.

3. The anti-cracking road concrete according to claim 2, characterized in that: The weight ratio of the ethylene-vinyl acetate copolymer to the hydroxyoctacosanol hydroxystearate is 2-5:

1.

4. The anti-cracking road concrete according to claim 1, characterized in that: The carbon fiber powder is modified carbon fiber powder, and the raw materials of the modified carbon fiber powder include carbon fiber powder and 2-acetamidoacrylic acid.

5. The anti-cracking road concrete according to claim 4, characterized in that: The weight ratio of the carbon fiber powder to 2-acetamidoacrylic acid is 20:1-3.

6. The anti-cracking road concrete according to claim 4, characterized in that: The preparation method of the modified carbon fiber powder comprises the following steps: dissolving the 2-acetamidoacrylic acid in ethanol, adding the carbon fiber powder, mixing evenly, and drying to obtain the modified carbon fiber powder.

7. The anti-cracking road concrete according to claim 1, characterized in that: The crushed stone is one or more of basalt crushed stone, diabase crushed stone and granite crushed stone.

8. The anti-cracking road concrete according to claim 1, characterized in that: The medium sand is one or both of quartz sand and basalt sand.

9. The anti-cracking road concrete according to claim 1, characterized in that: The waste asphalt material comes from Grade III aged petroleum asphalt pavement, and has a viscosity value of 1.5-1.9 Pa.s at 135°C and a needle penetration value of 18-23 at 25°C.

10. The method for preparing crack-resistant road concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preheat the remaining components except asphalt and additives, mix them evenly, and obtain a mixture; S2. Evenly mix the mixture, the asphalt and the additive to obtain the anti-cracking road concrete.

Citation Information

Patent Citations

  • Recycled asphalt concrete and preparation method thereof

    CN116621507A

  • Asphalt concrete with good rutting resistance and preparation method thereof

    CN118344099A

  • High-strength asphalt concrete and preparation method thereof

    CN119263702A

  • Modified-Asphalt Concrete Compositions for Roads Using Styrene Ethylene Butylene Styrene and Constructing Methods Using Thereof

    KR102207052B1

  • Modified lecithin for asphalt applications

    US11820786B2